1989
DOI: 10.1677/joe.0.1210375
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone concentrations in samples of saliva from adolescent girls living in Britain and Thailand, two countries where women are at widely differing risk of breast cancer

Abstract: Menstrual-cycle patterns of salivary progesterone concentration were obtained for 131 and 245 adolescent girls up to 4 years postmenarche living in Britain and Thailand respectively. These patterns were graded on a scale of 1 (little or no activity) to 5 (activity similar to that exhibited by the mature premenopausal woman) and the frequency of these grades within groups of girls from each centre was analysed. The major finding was that British girls exhibited a predominance of higher grades of progesterone ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, follicular progesterone was lower in those with menarche either 11 or 14 years of age, and menarcheal age was not related to any luteal-progesterone index. Particularly revealing, even when matched for chronological and gynecological age (time since menarche), British girls had higher levels of progesterone than Thai girls (Danutra et al, 1989). Clearly, whatever factors shape menarcheal age and/or ovarian steroid levels, these two aspects of ovarian functioning can vary independently to some degree.…”
Section: Dietary Composition Despite Vast Differences In Diets Mostmentioning
confidence: 98%
“…However, follicular progesterone was lower in those with menarche either 11 or 14 years of age, and menarcheal age was not related to any luteal-progesterone index. Particularly revealing, even when matched for chronological and gynecological age (time since menarche), British girls had higher levels of progesterone than Thai girls (Danutra et al, 1989). Clearly, whatever factors shape menarcheal age and/or ovarian steroid levels, these two aspects of ovarian functioning can vary independently to some degree.…”
Section: Dietary Composition Despite Vast Differences In Diets Mostmentioning
confidence: 98%
“…The phyto‐estrogens genistein and daidzein may well beneficially influence male puberty. A Western diet lowers the age of menarche – there are marked differences in the onset of hormone secretion and ovulatory cycles between girls in Britain and Thailand 56,57 – and may influence the LH‐RH pulse generator in males.…”
Section: Adolescence Puberty and Sexualitymentioning
confidence: 99%
“…However, plasma Pg levels among the groups were similar, which corresponds with the findings of Rose et al (22 ), who measured Pg in plasma collected during the luteal phase in women on bran diets. Danutra et al (32) found differences in extent of Pg activity in saliva from adolescent girls living in Britain and Thailand. The age at which Pg secretion was established was earlier for the British girls than for the Thai girls.…”
Section: Discussionmentioning
confidence: 99%